2017
DOI: 10.1007/s00234-017-1899-7
|View full text |Cite
|
Sign up to set email alerts
|

Response Assessment in Neuro-Oncology criteria, contrast enhancement and perfusion MRI for assessing progression in glioblastoma

Abstract: In conclusion, our findings suggest that CE-3D criterion is not yet suitable to assess progression in routine clinical practice. Indeed, the accurate threshold is still not well defined. To date, in our opinion, early detection of disease progression by RANO combined with advanced MRI imaging techniques like MRI perfusion and diffusion remains the best way to assess disease progression. Further investigations that would examine the impact of treatment modifications after progression determined by different cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Izquierdo et al (35) have reported that mean tumor diameter of low-grade glioma progressively decreased in most patients (94.4%) with a median slope of -5.7 mm/year (range=-14.84 to -0.85 mm/year) and for a median duration of 23 months after TMZ treatment. In GBM, median time to progression according to the Response Assessment in Neuro-Oncology (RANO) criteria was 6.4 months (36). These results suggested that our patients had refractory tumors against TMZ.…”
Section: Discussionmentioning
confidence: 70%
“…Izquierdo et al (35) have reported that mean tumor diameter of low-grade glioma progressively decreased in most patients (94.4%) with a median slope of -5.7 mm/year (range=-14.84 to -0.85 mm/year) and for a median duration of 23 months after TMZ treatment. In GBM, median time to progression according to the Response Assessment in Neuro-Oncology (RANO) criteria was 6.4 months (36). These results suggested that our patients had refractory tumors against TMZ.…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, experts seem to be required for non-enhancing tumor segmentation in non-glioblastomas on MRI at progression. MRIs at progression of non-glioblastomas are difficult to interpret because these suffer from artefacts from radiation therapy that cannot be discerned from disease progression ( Tensaouti et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For glioblastomas, the spatial overlap agreement between raters was high on preoperative MRI, which is not surprising due to the unambiguous distinction of contrast enhancing tumor to non-enhancing surrounding tissue. At progression the contrast becomes more ambiguous due to treatment effects such as pseudo-progression or radiation induced necrosis ( Tensaouti et al, 2017 ). The contrast becomes even more ambiguous on postoperative MRI with small fragmented residual tumor in the presence of surgical artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…While this article focuses on reporting results from the HERBY trial as performed, the newer proposed assessments can also be applied retrospectively to the HERBY imaging data, which may better characterize the imaging assessment. In addition to these modified and more quantitative metrics derivable from structural MR imaging, other quantitative metrics can be extracted from the multimodal imaging, 12,[18][19][20][21][22][23] building on the qualitative radiologic assessment performed here, 5 to inform on their value in pediatric response assessment. This will form the basis for ongoing evaluation of data from the HERBY study.…”
Section: Discussionmentioning
confidence: 99%